TENTANG MEDAN ELEKTROMAGNETIK RELATIVISTIK DI BINTANG NEUTRON YANG BEROTASI LAMBAT - , Atsnaita Yasrina, Dr.rer.nat. M. Farchani Rosyid ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study of the dynamics of magnetic field in neutron stars is a research topic that become interest of theoretical as well as observational astropysicists, especially the study of the phenomena where the magnetic field is screened by accreted matter around the neutron star. To understand such phenomena theoretically we require an equation which describes the dynamics at the magnetic field. Neutron stars are relativistic and rotating object. It is the fundamental reason for us to analyze the dynamics of the magnetic field relativistically. In this study the electromagnetic field equations are formulated in a state of dynamic maps of a stationary magnetic field around a neutron star that rotates slowly in the frame work of general relativity. We have derived the general relativistic version of Maxwell equation in the context of the metric of space time araound neutron stars.